Experiencia laboral y su repercusión en la contratación del personal administrativo - Macias Cedeño, Esther Salomé (2020)
The present case study was carried out by Christian Organization called “Principe de Paz” from the Palestinian Canton -Guayas -Ecuador the same one that has as mission to achieve the Missionary Development from its origin in order to extend and reach the places where there are spiritual needs as well as material. This organization is of private character and thus fulfils the obligations of the government, so also for the development of this study it was necessary to use the deductive method since through it was possible to acquire knowledge ranging from the general to the specific, through a survey, accurate and relevant information was collected in such a way that it also aims to determine the impact of work experience on the recruitment of administrative staff. The research achievements expressed that, not having work experience can become a maximum challenge to easily obtain a position in the organization even more in the area of administration functions, since it takes a lot of experience to be able to carry out the tasks entrusted to it and at the same time ensure that they are carried out correctly.